Reinforcing in the Production of Gypsum Materials on Base Basalt Fibers - Xolmuradovich, Ortiqov Shodiyor (European Journal of Life Safety and Stability (2660-9630), 2022)
There are given properties of testing in nano-lab-testing and using it in gypsum materials nowadays. The addition of basalt to the gypsum is carried out as follows: it is poured into the dry consist and mixed. Thus, the addition of basalt reduces shrinkage deformations and improves the technological properties of dry mixes.